Effects of Hydroxypropyl-Beta-Cyclodextrin on Cultured Brain Endothelial Cells - Szilvia Veszelka; Mária Mészáros; Gergő Porkoláb; Ágnes Rusznyák; Katalin Szászné Réti-Nagy; Mária A. Deli; Miklós Vecsernyés; Ildikó Bácskay; Judit Váradi; Ferenc Fenyvesi (Molecules, 2022)
The application of 2-hydroxypropyl-beta-cyclodextrin (HPBCD) in the treatment of the rare cholesterol and lipid storage disorder Niemann–Pick disease type C opened new perspectives in the development of an efficient therapy. Even if the systemic administration of HPBCD was found to be effective, its low permeability across the blood–brain barrier (BBB) limited the positive neurological effects. Nevertheless, the cellular interactions of HPBCD with brain capillary endothelial cells have not been investigated in detail. In this study, the cytotoxicity, permeability, and cellular internalization of HPBCD on primary rat and immortalized human (hCMEC/D3) brain capillary endothelial cells were investigated. HPBCD shows no cytotoxicity on endothelial cells up to 100 µM, measured by impedance kinetics. Using a fluorescent derivative of HPBCD (FITC-HPBCD) the permeability measurements reveal that on an in vitro triple co-culture BBB model, FITC-HPBCD has low permeability, 0.50 × 10−6 cm/s, while on hCMEC/D3 cell layers, the permeability is higher, 1.86 × 10−5 cm/s. FITC-HPBCD enters brain capillary endothelial cells, is detected in cytoplasmic vesicles and rarely localized in lysosomes. The cellular internalization of HPBCD at the BBB can help to develop new strategies for improved HPBCD effects after systemic administration.